On the Steady-State System Size Distribution for a Discrete-Time Geo/G/1 Repairable Queue. (19th March 2014) - Liu, Renbin; Deng, Zhaohui
Abstract : This paper studies a discrete-time N-policy Geo/G/1 queueing system with feedback and repairable server. With a probabilistic analysis method and renewal process theory, the steady-state system size distribution is derived. Further, the steady-state system size distribution derived in this work is extremely suitable for numerical calculations. Numerical example illustrates the important application of steady-state system size distribution in system capacity design for a network access proxy system.